Empirically supported treatments in psychotherapy: towards an evidence-based or evidence-biased psychology in clinical settings? - Castelnuovo, Gianluca (Frontiers in Psychology, 2010)
The field of research and practice in psychotherapy has been deeply influenced by two different approaches: the empirically supported treatments (ESTs) movement, linked with the evidence-based medicine (EBM) perspective and the “Common Factors” approach, typically connected with the “Dodo Bird Verdict”. About the first perspective, since 1998 a list of ESTs has been established in mental health field. Criterions for “well-established” and “probably efficacious” treatments have arisen. The development of these kinds of paradigms was motivated by the emergence of a “managerial” approach and related systems for remuneration also for mental health providers and for insurance companies. In this article ESTs will be presented underlining also some possible criticisms. Finally complementary approaches, that could add different evidence in the psychotherapy research in comparison with traditional EBM approach, are presented.